A Projection-Type Method for Multivalued Variational Inequality. (25th September 2013) - Fang, Changjie; Chen, Shenglan; Zheng, Jiming
Abstract : We propose a projection-type method for multivalued variational inequality. The iteration sequence generated by the algorithm is proven to be globally convergent to a solution, provided that the multivalued mapping is continuous with nonempty compact convex values. Moreover, we present a necessary and sufficient condition on the nonemptiness of the solution set. Preliminary computational experience is also reported.